2023
DOI: 10.1002/andp.202200594
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Resonant Axion Haloscopes to Quantum Electromagnetodynamics

Abstract: Recently, interactions between putative axions and magnetic monopoles have been revisited by two of the authors.[1] It is shown that significant modifications to conventional axion electrodynamics arise due to these interactions, so that the axion–photon coupling parameter space is expanded from one parameter to three . Poynting theorem is implemented to determine how to exhibit sensitivity to and using resonant haloscopes, allowing new techniques to search for axions and a possible indirect way to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In resonant haloscopes with an applied magnetic field, the g aAB term creates a magnetic current analogue to the well-known g a𝛾𝛾 term's displacement current. Implementing Poynting theorem, [69] it has been shown that the signal power expected on resonance in a haloscope due to this additional term is given by [27] P aAB = Close-up on the dark-photon kinetic mixing limits from ORGAN Phase 1a at 95% CL (red), plotted against exclusion limits from ORPHEUS (90% CL), [70] DOSUE-RR (95% CL) [71] (gray) and the cosmological bound that dark photons must meet in order to be dark matter [29,[72][73][74][75] (blue). We show the limits assuming the fixed polarization scenario as opaque, and the less-conservative random polarization scenario as transparent (see ref.…”
Section: Qemd Electromagnetic Couplingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In resonant haloscopes with an applied magnetic field, the g aAB term creates a magnetic current analogue to the well-known g a𝛾𝛾 term's displacement current. Implementing Poynting theorem, [69] it has been shown that the signal power expected on resonance in a haloscope due to this additional term is given by [27] P aAB = Close-up on the dark-photon kinetic mixing limits from ORGAN Phase 1a at 95% CL (red), plotted against exclusion limits from ORPHEUS (90% CL), [70] DOSUE-RR (95% CL) [71] (gray) and the cosmological bound that dark photons must meet in order to be dark matter [29,[72][73][74][75] (blue). We show the limits assuming the fixed polarization scenario as opaque, and the less-conservative random polarization scenario as transparent (see ref.…”
Section: Qemd Electromagnetic Couplingsmentioning
confidence: 99%
“…In resonant haloscopes with an applied magnetic field, the gaAB$g_{aAB}$ term creates a magnetic current analogue to the well‐known gaγγ$g_{a\gamma \gamma }$ term's displacement current. Implementing Poynting theorem, [ 69 ] it has been shown that the signal power expected on resonance in a haloscope due to this additional term is given by [ 27 ] PaABbadbreak=()gaAB2ρama()β1+βB02VCaABQnormalL$$\begin{equation} P_{aAB}={\left(g_{aAB}^2 \frac{\rho _{\text{a}}}{m_{\text{a}}}\right)}{\left(\frac{\beta }{1+\beta } B_0^2 V C_{aAB} Q_{\mathrm{L}}\right)} \end{equation}$$where CaAB$C_{aAB}$ is another form factor, coincidentally of identical form to Cϕ$C_{\phi }$ as presented in Equation (10). Consequently, limits placed by haloscopes on the dilaton coupling gϕγγ$g_{\phi \gamma \gamma }$ are equivalent to limits on gaAB$g_{aAB}$.…”
Section: Alternate Dark Matter Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…a Alternative fazor formulation of the Poynting theorem in terms of complex fields allows in the complex valued energy balance equation the separation of the reactive and dissipative parts of the energy transfer. 32,33 supplemented with the initial conditions…”
Section: Axion-photon Couplings In Effective Electro-magneto Dynamicsmentioning
confidence: 99%
“…The fact that axion electrodynamics breaks electric-magnetic duality has spurred some authors to propose non-standard formulations of axion electrodynamics, which aim to either restore electric-magnetic duality [13] or break it in alternative ways [14][15][16]. These non-standard formulations of axion electrodynamics not only allow for g aγγ ∝ 1/e 2 , implying much stronger couplings, they also introduce new terms in (1.3); for example, allowing E ∂a ∂t to source ∇ × E. Some of the proposed modifications have begun to receive attention in the context of the design or interpretation of experiments [17][18][19][20][21][22][23][24][25][26][27][28] or astrophysical observations [29]. Thus, it is important to understand to what extent such a non-standard axion electrodynamics is theoretically and phenomenologically viable.…”
Section: Introduction and Central Argumentmentioning
confidence: 99%